Which One Is More Effective for Lower Urinary Tract Dysfunctions in Children? Pelvic Floor Contraction or Pelvic Floor Relaxation in Biofeedback Therapy - Burak Köprü; Turgay Ebiloğlu; Giray Ergin; Engin Kaya; Yusuf Kibar (Journal of Urological Surgery)

(untitled)
Objective:The objective of this study is to investigate the results of contraction- and relaxation-based biofeedback (BF) in children with lower urinary tract dysfunction (LUTD).Materials and Methods:Between 2007 and 2017, we randomly directed children with the diagnosis of LUTD and refractory to standard urotherapy modifications via BF by using two different animations: animation A with relaxation nature BF (RBF) and animation B with contraction nature BF (CBF). The categories of non-response, partial response, and full response were defined as a 0-49% decrease, 50-99% decrease, and 100% decrease in the LUTD Symptom score, respectively. Results of biofeedback using RBF or CBF were compared.Results:There were 100 and 70 children in the RBF and CBF groups, respectively. Patients with an abnormal voiding pattern (abnormalVP) and a positive electromyography (EMG) activity (positive EMG) had a better resolution with RBF (p=0.001), whereas patients with abnormalVP and a negative EMG activity (negative EMG) had a better resolution with CBF (p=0.039). Despite being statistically insignificant, patients with a normal voiding pattern (normalVP) and positive EMG had a better resolution with CBF (p=0.452), whereas patients with normalVP and negative EMG had a better resolution with RBF (p=0.083).Conclusion:The EMG activity identifies the BF nature in children with LUTD and abnormalVP. Importantly, positive EMG had better results with RBF, whereas negative EMG had better results with CBF.